Design and Construction of a Solar Power Plant (PLTS) in the 3T rea Tourist Houses of Gangga Murmas Trees Lombok Utara - Falah, Moh. Zainul; Wahyu Tri Handoko; Ryan Kurniawan (Tinta Emas Publisher, 2023)
Indonesia has great potential for the development of Solar Power Plants (PLTS) thanks to its geographical condition which is located in a tropical area with sunshine all year round Average Daily Irradiation: Around 5-6 kWh/m² per day. This research aims to design and build an Off Grid Solar Power Plant (PLTS) that can meet electrical energy needs in underdeveloped, frontier and outermost areas (3T) in the Gangga Murmas Tree House tourist area, Lombok Utara. This area is known to have limited access to electricity from the main network, so the implementation of an Off Grid PLTS system is considered an effective and sustainable solution. The research method involves field surveys to identify environmental characteristics, energy needs, and electricity consumption patterns in the area. Next, an Off Grid PLTS system design analysis was carried out which included the selection of main components such as solar panels, energy storage batteries and charging controllers. System testing and evaluation is carried out to ensure optimal performance under local environmental conditions. It is hoped that the results of this research can make a significant contribution to the development of renewable energy in the 3T area, increase electricity accessibility, and support the sustainability of the Gangga Murmas Tree House tourist area. This PLTS is designed to meet electricity needs related to lighting at night in this tourist area, where currently there is no lighting at night. The power generated is 600 Wph with an electricity requirement of 120 Wh for 12 hours.